Gefängnis als Schwellenraum in der byzantinischen Hagiographie Eine Untersuchung früh- und mittelbyzantinischer Märtyrerakten - Papavarnavas, Christodoulos (Millennium-Studien / Millennium Studies, 2021)
This volume investigates the literary depiction of prison as a liminal space in early and middle Byzantine martyrs' Passions. Prison proves to be a transitional space where both the formation of corporeal endurance and the spiritual maturation of the protagonists take place, contributing to their identity as martyrs. The aspects examined here include terminology, narrative structure, gender, emotions and the senses.